A Hierarchical Failure Detection Service with Perfect Semantics - Brasileiro, Francisco V.; Figueiredo, Jorge C. A. de; Sampaio, Lívia M. R. (Anais do Workshop de Testes e Tolerância a Falhas (WTF), 2002)
A failure detector is an important abstraction to support the implementation f higher level fault-tolerant protocols on distributed asynchronous systems. In this paper we show, via a counter example, that using the best possible failure detector of a given class is not always the key to achieve the best performance for a specific higher level consensus protocol. We argument that this behaviour is due to structural limitations of the consensus protocol that are unlikely to be circumvented, unless stronger abstractions are provided. Thus, we advocate that the designer of a generic failure detection service should concentrate her efforts in implementing the strongest failure detector possible - even if it is not the best within its class, instead of trying to implement the fest failure detector of a weaker class. Following this philosophy, we present the bases of the design of a hierarchical failure detection service with the strongest semantics known, namely that of a perfect failure detector.